RESTORATIVE JUSTICE IN THE SETTLEMENT OF TRAFFIC ACCIDENT CAUSING DEATH TOLL ACCORDING TO THE PERSPECTIVE OF CUSTOMARY JUDICIARY IN SANGGAU DISTRICT, WEST KALIMANTAN - Marina Rona; Rachmad Safa’at; Abdul Madjid; Mohammad Fadli (Faculty of Law, Universitas Sebelas Maret, 2020)
This research aims to examine restorative justice in the settlement of traffic accidents caused by the death toll from the customary judiciary perspective in Sanggau Regency, West Kalimantan. The fact of the field shows that a customary judiciary is an option for indigenous people to settle traffic accidents that resulted in the death according to customary decision. The customary judicial process is led by Pomuntuh Adat with deliberation for consensus involving the perpetrators/drivers and heirs of his family and heirs of the victim's family. Adat decision by punishing perpetrators to repay or reinstate victims losses due to criminal acts sanctioned the customary verdict where the perpetrators/drivers and heirs of the family pay customary fines to the heirs of the victim's family and also perform customary rituals as a form of recovery of natural balance. The matter of traffic accident that has been decided through the customary judiciary, it is not processed through the process through the state's prejustice. The research is an empirical legal research, using secondary data through literature studies. Primary Data was obtained through interviews where the results concluded that the settlement of a traffic accident resulting in a death toll in a customary judicial perspective is a real manifestation of restorative justice